Inclusão digital no Centro Vocacional Tecnológico Henfil: uma leitura sob a ótica do capitalismo informacional - Rogério Luís Massensini (2010)
This work analyzed the digital inclusion social program developed by the Henfil vocational Center with the objective of evaluating opportunities and limitations for its users. This social program is promoted by the Federal Government in a partnership with the State Government of Minas Gerais and the city hall of Ribeirão das Naves through the Ministry of Science and Technology MCT, the Science, Technology and Higher Education Office SECTES, the Science and Technology Office for Social Inclusion SECTIS and the Education Office in Ribeirão das Neves. This research relies on the theoretical support of the authors who discuss social inclusion such as Bernardo Sorj, Christine Bruce and Mark Warschauer. They claim that in order to promote social inclusion, equipment, infrastructure, training, qualification and critical use of informatics and information through information literacy should be in place. In addition, a historical systematization of the capitalist development and information capitalism was included in the analysis as well as the different aspects and specificities of the concept of marginalization and social exclusion. Theoretical contributions were also collected from the area of Information Sciences and other Social Sciences so as to understand this social reality. A fieldwork was carried out based on the fundamentals of ethnography and by adopting the following techniques: participant observation, interviews, questionnaires, document analysis. Results show that the CVT Henfil digital inclusion social program presents possibilities of creating opportunities for social inclusion, which may well contribute, to the students social inclusion. Data also shows that a program curriculum adapted to the local reality is necessary since the students context, social and material conditions must be taken into account in the program and in the teaching-learning process. This emphasis comes from the need to provide information literacy to all, that is, to enable subjects to go beyond technical domains and use information critically. Hence the need to invest heavily in educating subjects through information literacy and helping them build critical perspectives on the world and on the digital space.